Humanized COVID‐19 decoy antibody effectively blocks viral entry and prevents SARS‐CoV‐2 infection. Issue 1 (30th November 2020) - Huang, Kuo‐Yen; Lin, Ming‐Shiu; Kuo, Ting‐Chun; Chen, Ci‐Ling; Lin, Chung‐Chih; Chou, Yu‐Chi; Chao, Tai‐Ling; Pang, Yu‐Hao; Kao, Han‐Chieh; Huang, Rih‐Sheng; Lin, Steven; Chang, Sui‐Yuan; et al.
Abstract: To circumvent the devastating pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, a humanized decoy antibody (ACE2‐Fc fusion protein) was designed to target the interaction between viral spike protein and its cellular receptor, angiotensin‐converting enzyme 2 (ACE2). First, we demonstrated that ACE2‐Fc could specifically abrogate virus replication by blocking the entry of SARS‐CoV‐2 spike‐expressing pseudotyped virus into both ACE2‐expressing lung cells and lung organoids. The impairment of viral entry was not affected by virus variants, since efficient inhibition was also observed in six SARS‐CoV‐2 clinical strains, including the D614G variants which have been shown to exhibit increased infectivity. The preservation of peptidase activity also enables ACE2‐Fc to reduce the angiotensin II‐mediated cytokine cascade. Furthermore, this Fc domain of ACE2‐Fc was shown to activate NK cell degranulation after co‐incubation with Spike‐expressing H1975 cells. These promising characteristics potentiate the therapeutic prospects of ACE2‐Fc as an effective treatment for COVID‐19. Synopsis: Currently, there is no effective strategy to fight against the COVID‐19 pandemic. We aim to design and develop a humanized decoy antibody to block SARS‐CoV‐2 infection. The ACE2‐Fc fusion protein can form a dimer that mimics a humanized antibody and specifically binds to the SARS‐CoV‐2 Spike protein. The ACE2‐Fc fusion protein abrogates virus replication by blocking SARS‐CoV‐2 entry in clinical isolates. The peptidase activity of ACE2‐Fc enables the decoy antibody to reduce angiotensin II‐mediated cytokine cascade. After binding to Spike‐expressing target cells, ACE2‐Fc activates degranulation of NK cells. Abstract : Currently, there is no effective strategy to fight against the COVID‐19 pandemic. We aim to design and develop a humanized decoy antibody to block SARS‐CoV‐2 infection.